2021
DOI: 10.1016/j.jtho.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of KRAS G12C Mutation in Patients With NSCLC: Results From the European Thoracic Oncology Platform Lungscape Project

Abstract: Introduction: KRAS mutations, the most frequent gain-offunction alterations in NSCLC, are currently emerging as potential predictive therapeutic targets. The role of KRAS-G12C (Kr_G12C) is of special interest after the recent discovery and preclinical analyses of two different Kr_G12C covalent inhibitors (AMG-510, MRTX849).Methods: KRAS mutations were evaluated in formalin-fixed, paraffin-embedded tissue sections by a microfluidic-based multiplex polymerase chain reaction platform as a component of the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
(37 reference statements)
3
26
0
Order By: Relevance
“…These findings are consistent with earlier studies in smaller populations showing that KRAS mutations, specifically the p.G12C mutation, are highly prevalent among current or former smokers, and that this mutation is associated with a high rate of brain metastases [18,20,30,31]. Similarly, the KRAS p.G12C mutation was found to be higher in current and former smokers in a large European data set in patients with earlier stage disease (stage Ia to IIIb NSCLC) [32]. Other studies have also demonstrated that nonsquamous cell carcinoma is the most common histology type associated with KRAS mutations in general, as well as KRAS p.G12C specifically [30,33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with earlier studies in smaller populations showing that KRAS mutations, specifically the p.G12C mutation, are highly prevalent among current or former smokers, and that this mutation is associated with a high rate of brain metastases [18,20,30,31]. Similarly, the KRAS p.G12C mutation was found to be higher in current and former smokers in a large European data set in patients with earlier stage disease (stage Ia to IIIb NSCLC) [32]. Other studies have also demonstrated that nonsquamous cell carcinoma is the most common histology type associated with KRAS mutations in general, as well as KRAS p.G12C specifically [30,33].…”
Section: Discussionsupporting
confidence: 92%
“…This similarity in outcomes is consistent with other studies showing that in Western populations, the KRAS p.G12C mutation is not predictive of outcomes in patients with advanced NSCLC [17][18][19][20]39]. In earlier stage NSCLC, KRAS p.G12C mutations were associated with a trend toward shorter overall survival than those without KRAS mutations [32]. Taken together, these findings reflect an unmet need for effective treatments for patients with KRAS p.G12C mutation in both early and advanced NSCLC.…”
Section: Discussionsupporting
confidence: 89%
“…These co-mutation partners lead to variances in gene expression and distinct patterns of inflammatory and immunecheckpoint molecules release, which models the tumor microenvironment and promotes different responses to therapies (12,17). Because of this tumor heterogeneity, the prognostic role of KRAS mutant cancers remains uncertain, although most studies report a major aggressive behavior of this type of cancer (18)(19)(20).…”
Section: Kras-mutant Lung Cancer Is a Heterogeneous Disease And Has A...mentioning
confidence: 99%
“…Mutations of the v-Ki-ras2 Kirsten rat sarcoma viral oncogene homology gene ( KRAS ) gene are the most common oncogenic drivers of non-squamous non-small cell lung carcinoma (NSCLC) and occur in approximately 25–38% of non-Asian and 8–10% of Asian lung adenocarcinoma patients [ 1 , 2 , 3 ]. Although associated with smoking, KRAS mutations also occur in approximately 5–15% of never-smoking patients [ 1 , 4 ]. KRAS ’ role as a prognostic factor has been investigated in numerous studies, but with conflicting results [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%